2022
DOI: 10.3390/plants11131688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Intensity on Morphology, Photosynthesis and Carbon Metabolism of Alfalfa (Medicago sativa) Seedlings

Abstract: To understand how light intensity influences plant morphology and photosynthesis in the forage crop alfalfa (Medicago sativa L. cv. Zhongmu 1), we investigated changes in leaf angle orientation, chlorophyll fluorescence, parameters of photosynthesis and expression of genes related to enzymes involved in photosynthesis, the Calvin cycle and carbon metabolism in alfalfa seedlings exposed to five light intensities (100, 200, 300, 400 and 500 μmol m−2 s−1) under hydroponic conditions. Seedlings grown under low lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 66 publications
5
27
0
Order By: Relevance
“…In this study, the soluble sugar content of alfalfa during a 30‐day harvest period exhibited a consistent upward trend in response to greater light intensity, corroborating the findings reported by Tang et al. (2022). Higher light intensity increased the specific leaf weight and net photosynthetic rate of alfalfa leaves, thereby facilitating the accumulation of photosynthetic products in the leaves.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the soluble sugar content of alfalfa during a 30‐day harvest period exhibited a consistent upward trend in response to greater light intensity, corroborating the findings reported by Tang et al. (2022). Higher light intensity increased the specific leaf weight and net photosynthetic rate of alfalfa leaves, thereby facilitating the accumulation of photosynthetic products in the leaves.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, Tang et al. (2022) reported a continuous decrease in alfalfa plant height from 100 to 500 µmol m −2 s −1 under LED white light, which may be attributed to the shade avoidance syndrome triggered by the high‐light treatment during the early stages of plant growth. In summary, both low and high‐light intensities are not viable for alfalfa cultivation in a PFAL setting.…”
Section: Discussionmentioning
confidence: 96%
“…A severe reduction in morphological growth under salinity stress can be attributed to the limitation of the physiological performance of stressed plants due to a decrease in their photosynthetic ability (Chaudhry and Sidhu, 2022). Biomass accumulation is determined by assimilate production as a result of photosynthesis, which in turn is governed by the chlorophyll pigment content, A and T (Li et al, 2021, Tang et al, 2022). It was observed that highly salt‐tolerant (HST) genotypes maintained a higher content of chlorophyll pigments, A , T and also had better stomatal conductance, as seen by a lower leaf surface temperature compared to salt‐susceptible genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…When subjected to low light levels, plants exhibit a notable response by reducing the thickness of their leaves (Wei et al 2023). Research highlights that low light intensity correlates with an increase in leaf area (Tang et al 2022). Additionally, low light intensity also hinders the photosynthetic capacity of plant leaves and reduces their capacity to accumulate photosynthetic materials (Xiang et al 2021).…”
Section: Introductionmentioning
confidence: 99%